2008
DOI: 10.1186/1471-2407-8-385
|View full text |Cite
|
Sign up to set email alerts
|

Genetic analysis of the vitamin D receptor gene in two epithelial cancers: melanoma and breast cancer case-control studies

Abstract: Background: Vitamin D serum levels have been found to be related to sun exposure and diet, together with cell differentiation, growth control and consequently, cancer risk. Vitamin D receptor (VDR) genotypes may influence cancer risk; however, no epidemiological studies in sporadic breast cancer (BC) or malignant melanoma (MM) have been performed in a southern European population. In this study, the VDR gene has been evaluated in two epithelial cancers BC and MM.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
42
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(49 citation statements)
references
References 35 publications
6
42
1
Order By: Relevance
“…They found a modest significantly increase in breast cancer risk associated with the ff genotype (OR ¼ 1.16, 95%CI: 1.04-1.28). Similar results were found in three further studies (Barroso et al, 2008;Gapska et al, 2009;Sinotte et al, 2008). Only one study (Anderson, Cotterchio, Cole, & Knight, 2011) found a significant inverse association of FokI ff genotype with breast cancer risk (OR ¼ 0.71, 95%CI: 0.57-0.88).…”
Section: Breast Cancersupporting
confidence: 87%
“…They found a modest significantly increase in breast cancer risk associated with the ff genotype (OR ¼ 1.16, 95%CI: 1.04-1.28). Similar results were found in three further studies (Barroso et al, 2008;Gapska et al, 2009;Sinotte et al, 2008). Only one study (Anderson, Cotterchio, Cole, & Knight, 2011) found a significant inverse association of FokI ff genotype with breast cancer risk (OR ¼ 0.71, 95%CI: 0.57-0.88).…”
Section: Breast Cancersupporting
confidence: 87%
“…Several earlier studies similarly failed to reveal an impact of VDR polymorphisms on coronary artery disease [41] or malignancy [42,43,44,45]. Other studies, however, did show an impact of VDR polymorphisms on the prevalence of diabetes mellitus [24,25], diabetic nephropathy [24] and malignancy [33,34,35,36,37,38,45,81]. Specifically, Fok1 VDR polymorphisms have been reported to impact on breast, prostate, skin, colorectum, ovary and bladder cancer with strongest impact on breast cancer, prostate cancer and malignant melanoma [45].…”
Section: Discussionmentioning
confidence: 92%
“…Polymorphisms of VDR have been reported to be associated with bone mineral density [23] diabetes mellitus [24,25], hypertension [26], asthma [27,28], periodontitis [29,30], risk of multiple sclerosis [31,32] and malignancy [33,34,35,36,37,38]. On the other hand, several studies failed to report an impact of VDR polymorphisms on multiple sclerosis [39], inflammatory bowel disease [40], coronary artery disease [41] or malignancy [42,43,44].…”
Section: Introductionmentioning
confidence: 99%
“…It was proposed that the Vitamin D Receptor (VDR) gene might play a role in melanoma development as well, since its interaction with the calcitriol ligand results in antiproliferative and pro-differentiation signals on melanocytes. Rare VDR alleles were found more commonly in melanoma cases than controls, although conflicting evidence were also reported (Barroso et al, 2008;Hutchinson et al, 2000). All these evidence stress the fact that melanoma, being a multifactorial disease, is characterized by a heterogeneous genetic background and further investigations on melanoma-predisposing genes are necessary to gain new insights into this overwhelming wealth of information and, in turn, to the comprehension of melanoma pathogenesis.…”
Section: Other Genesmentioning
confidence: 92%